PENGARUH TERAPI HYPNOPUNTURBREASTFEEDING DAN AIR SEDUHAN DAUN KELOR TERHADAP PRODUKSI ASI - Galih Setia Adi; Saelan Saelan (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Exclusive breastfeeding is conducted since a new baby was born. Currently, the coverage  of  exclusive  breastfeeding  for  babies  are  in aged  0-6  months,  in Indonesia there are 19 provinces whose the coverage is above the national average (54.3%). this number cannot reach 100%, therefore it is necessary to increase the coverage rate of breastfeeding in babies 0-6 months. These data prove that many mothers do not give their breast milk. This is due to several things such as; the breast milk does not coming out at the beginning of a baby's birth, a family which does not support the mother in breastfeeding, the jobs which make difficult to breastfeed. The research aimed to identify the effect of hypnopunturbreastfeeding therapy and Moringa leaves steeping water on breast milk  production  in  Sukoharjo.  The  research  design  used  pre  and  post  test control group in pure experimental research. The bivariate analysis used the Paired sample t-test. The results showed the differences in the giving of brest care therapy and water from Moringa leaves steeping water (control group) and  in  the  post  giving  hypnopunkturbresfeeding,  and  the  Moringa  leaves steeping water. It can be seen from the sig value 0.000 which smaller than 0.005. Keywords:     breast     milk     production,     Akupuntur,     Hypnobrestfeeding, Hypnopunturbreastfeeding, Moringa leaves steeping water